Reproductive site selection in the leaf-frog Phyllomedusa azurea Cope, 1862 (Anura: Hylidae) in altered areas of the Brazilian Cerrado - Dias, Tailise Marques; Maragno, Franciele Pereira; Prado, Cynthia P. A. [UNESP]; Cechin, Sonia Zanini (Taylor & Francis Ltd, 2014)
The selection of reproductive sites by anurans may be associated with each species' behavioural restrictions, reproductive modes, morphology and physiology. We investigated the use of reproductive sites by Phyllomedusa azurea in an area of Cerrado, Central-Western Brazil, which has been modified by agricultural and cattle ranching. Reproductive activity was studied during the peak of the rainy season in two consecutive years. No correlation was found between male body size and position of the calling site, and calling sites did not vary among ponds. Conversely, the height and distance from the water margin where clutches were found varied among ponds. Phyllomedusa azurea used mainly Brachiaria sp. and Brachiaria humidicola grasses as calling sites and the grass Brachiaria sp. and the shrub Melochia villosa (Malvaceae) as oviposition sites. Calling males used the vegetation according to its availability; however, individuals seemed to exhibit significant preferences regarding the type of vegetation used for oviposition.
Keywords: calling site; habitat selection; perch availability; oviposition site; Phyllomedusinae